Pemaknaan Dan Penerapan Prinsip Resiprositas Berdasarkan ASEAN Banking Integration Framework - Inda Rahadiyan (Jurnal Hukum IUS QUIA IUSTUM, 2019)
The reciprocity principle is the main principle in the integration of banking service in the ASEAN region, where it is scheduled to take place in 2020. The banking industry is complex and strictly regulated, therefore, research on the meaning of reciprocity in the ASEAN Banking Integration Framework (ABIF) becomes an interesting and relevant study. The problems examined in this study include: first, how are the meaning and the legal binding power of the reciprocity principle based on ABIF? Second, how is the Indonesian Government's effort to implement the reciprocity principle based on ABIF? This research was conducted by using normative method. The results of the study concluded that, first, the reciprocity principle based on ABIF is a basic principle of reciprocal treatment between member countries aimed at realizing ease of access and banking operational flexibility. This principle does not apply automatically and without conditions, but is based on the commitment and readiness of each country. Second, the Indonesian Government's efforts to implement the reciprocity principle have been carried out through the issuance of Law Number 4 of 2018 on the Ratification of the Protocol to Implement the Sixth Commitment Package in Financial Services in the ASEAN Framework in Services.